Mini Solar Water Heater - Azman, Muhamad Addin Muqaffa; Shahnizan, Sharil Haziq; Abdullah, Nurmina (Multidisciplinary Applied Research and Innovation, 2025)
This study presents the design and development of a cost-effective mini solar water heater intended to reduce electricity consumption while maintaining water temperature in a storage tank. The project addresses the high market price of conventional solar water heaters by creating an affordable solution for rural or remote areas with limited access to electricity. A flat-plate collector system was selected for its simplicity and efficiency, using recycled materials to minimize cost. Prototype testing demonstrated that the system could heat water up to 42 °C during peak sunlight hours and maintain a gradual temperature decrease over time. Although the target temperature of 50 °C was not achieved, the results confirm the feasibility of the design for low-cost water heating applications. The proposed system offers an environmentally friendly, user-friendly, and low-maintenance alternative for domestic water heating, with potential improvements including enhanced insulation, increased copper circulation, and integration of auxiliary heating to improve performance.